2016
DOI: 10.1063/1.4940878
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in layered half-metallic Heusler alloy superlattices

Abstract: We show that when two Heusler alloys are layered in the [001], [110], or [111] directions for various thicknesses to form a superlattice, the Slater-Pauling rule may still be satisfied and the resulting superlattice is often half-metallic with gaps comparable to or larger than those of its constituents. In addition, uniaxial magnetocrystalline anisotropy is induced because of the differences in the electronic structure of the two Heuslers in the superlattice. Various full-full, full-half, and half-half Heusler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…A separate sample series (not shown) grown only on MgO (001) substrates at 300 • C did not experience a spin reorientation transition below M S,crit , further supporting the conclusion that K ⊥ ef f is maximized for [CMA n /FMA n ] q with high aluminum excess grown on GaAs (001) at 150 • C with no subsequent anneal. This combines the advantages of the superlattice structure with compressive strain resulting in c/a > 1, both of which are expected to enhance K ⊥ M CA [8,17]. This factor is then allowed to dominate by increasing the aluminum content, thereby lowering the shape anisotropy contribution.…”
Section: B Magnetic Anisotropy Energymentioning
confidence: 99%
See 2 more Smart Citations
“…A separate sample series (not shown) grown only on MgO (001) substrates at 300 • C did not experience a spin reorientation transition below M S,crit , further supporting the conclusion that K ⊥ ef f is maximized for [CMA n /FMA n ] q with high aluminum excess grown on GaAs (001) at 150 • C with no subsequent anneal. This combines the advantages of the superlattice structure with compressive strain resulting in c/a > 1, both of which are expected to enhance K ⊥ M CA [8,17]. This factor is then allowed to dominate by increasing the aluminum content, thereby lowering the shape anisotropy contribution.…”
Section: B Magnetic Anisotropy Energymentioning
confidence: 99%
“…Recently, it was predicted that atomic superlattices of certain pairs of Heusler materials could be perpendicularly magnetized half-metals [8]. Heusler superlattices are distinct from other magnetic multilayers because they maintain the same crystal structure and, in many cases, several of the same atomic species in both constituent layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible existence of a dead interface magnetic layer lowering the magnetoresistive performances was moreover reported in the case of Co 2 MnGe/Rh 2 CuSn SVs [34]. Other Heusler-alloy-based heterostructures have mostly been studied numerically from first principles [35][36][37][38][39][40][41]. Chadov et al, in particular, proposed to select the best all-Heusler-alloy MTJs among those which minimize the mismatch between the atomic and the band structures of the electrode and spacer materials: They first decided to select the half-metallic electrode material Co 2 MnAl and further proposed to use CoVMnAl as the nonmagnetic insulating spacer [37].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that, in terms of lattice distortion, the HM properties of these alloys can be maintained in the range of −4.8% to 6.6% and −7.7% to 4.5%, respectively. The discovery of the presence of HM properties in HH alloys has led to the availability of more options for spintronics materials [26,27].…”
Section: Introductionmentioning
confidence: 99%